Cytotoxic Indole-Diterpenoids from the Marine-Derived Fungus Penicillium sp. KFD28 - Lu-Ting Dai (MDPI AG, 2021)
Four new indole-diterpenoids, named penerpenes K-N (1–4), along with twelve known ones (5–16), were isolated from the fermentation broth produced by adding L-tryptophan to the culture medium of the marine-derived fungus Penicillium sp. KFD28. The structures of the new compounds were elucidated extensively by 1D and 2D NMR, HRESIMS data spectroscopic analyses and ECD calculations. Compound 4 represents the second example of paxilline-type indole diterpene bearing a 1,3-dioxepane ring. Three compounds (4, 9, and 15) were cytotoxic to cancer cell lines, of which compound 9 was the most active and showed cytotoxic activity against the human liver cancer cell line BeL-7402 with an IC50 value of 5.3 μM. Moreover, six compounds (5, 7, 10, 12, 14, and 15) showed antibacterial activities against Staphylococcus aureus ATCC 6538 and Bacillus subtilis ATCC 6633.